Designing a Model for the Management of Modern Health Services of Middle-aged Adults in the Iranian Health System - Dabaghi, Fatemeh; Mahmoodi, Ghahraman; Dashtian, Azadeh Ahmadi; Shokri, Akbar (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
BACKGROUND: Middle adulthood can represent a peak stage of life if health is addressed comprehensively across all dimensions. This study aimed to develop an appropriate model for managing modern health services for middle-aged adults within the Iranian health system in 2019. METHODS: This mixed-method study was conducted in two phases. In the qualitative phase, the participants were 21 policymakers and experts involved in the middle-aged adults’ program at the Ministry of Health as well as provincial and county health centers, selected through purposive sampling. In the quantitative phase, 431 executives of the middle-aged adults’ program in Ardabil Province were enrolled. Data were analyzed using SPSS version 20 (Chicago, IL, USA) and Amos software. RESULTS: The mean age of participants was 35.41 ± 6.94 years. The Content Validity Ratio (CVR) was 0.79, and Cronbach’s alpha for the questionnaire was 0.95. Six key components of health service management were identified: human resources, financial resources, executive management, health service package, essential medicines and equipment, and community participation. CONCLUSIONS: The proposed model was most strongly influenced by human resources and the health service package, whereas community participation had the weakest impact. This model can serve as a guide for policymakers and health authorities to improve health indicators among middle-aged adults in Iran.